Menggagas Revolusi Mental Birokrasi Melalui Konsep Competitive Agile Leadership - Viky Aldin Hulu; Tistry Rahmatiwani Patuninno; Deva Puspasari; Nandy Juniyanto; Lidya Tri Adistia Pramudita (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2020)
The research is directed to formulate a bureaucratic mental revolution strategy by utilizing the concept of agile leadership. The research team formulated a bureaucratic mental revolution strategy by utilizing the concept of agile leadership through several stages. First, an analysis of the agile leadership model was carried out on the governance practices of Desa Majasarigovernment. Second, the analysis of agile government was conducted as a result of the emergence of agile leadership in the village. The results of the study explained that the existence of agile leadership is very important to encourage the emergence of agile government. That is, if the agile bureaucratic mentality is strongly supported by the existence of agile leadership. Seeing the paternalistic bureaucracy culture that the leader as the center of activity of the organization, bureaucracy mental revolution strategy has to start from a mental revolution from the leader. Leaders' mental revolution can be implemented when they are placed in a competitive agile leadership assessment system. Therefore, the research team offers and formulates a competitive model of agile leadership as a mental revolution strategy bureaucracy.